Counting Brand Equity of Islamic Higher Education in Indonesia : A High School and Islamic High School Students’ Perspective - Ahmad Juhaidi; Syaifuddin Syaifuddin (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The objectives of this study is to explore brand equity of Islamic higher education (IHE) in Indonesia. This research is field research with descriptive quantitative approach. The Brand equity is measured using Customer Based Brand Equity - Islamic Higher Education (CBE-IHE) : brand awareness, brand association, perceived quality, and brand loyalty. CBE-IHE is the average score of each brand equity asset from 0 to 4. Data were collected by questionnaire and distributed to 1100 students of high school (HS) and Islamic high school (IHS) and 1373 Lecturers/ staffs/ students of State Islamic University Antasari Banjarmasin. The finding are CBE-IHE’s  brand equity index is 2. 15 out of the highest index 4. Brand Awareness of IHE is mayor problem of IHE brand. This study shows IHE is not in top of mind of HS and HIS students